Cyclodextrin–polysaccharide-based, in situ-gelled system for ocular antifungal delivery - Fernández-Ferreiro, Anxo; Fernández Bargiela, Noelia; Varela, María Santiago; Martínez, Maria Gil; Pardo, Maria; Piñeiro Ces, Antonio; Méndez, José Blanco; Barcia, Miguel González; Lamas, Maria Jesus; Otero-Espinar, Francisco.J. (Beilstein Journal of Organic Chemistry, 2014)
Fluconazole was studied with two different hydrophilic cyclodextrins (hydroxypropyl-β-cyclodextrin (HPBCD) and sulfobutyl ether-β-cyclodextrin (SBECD)) for the formation of inclusion complexes. HPBCD and SBECD showed low cell cytotoxicity in human keratocytes as assessed by the label-free xCELLigence system for real-time monitoring. The fluconazole–HPBCD complex was incorporated into an ion-sensitive ophthalmic gel composed of the natural polysaccharides gellan gum and κ-carrageenan. This system showed good bioadhesive properties and effective control of fluconazole release.
Keywords: cyclodextrins; eye drops; fluconazole; hydroxypropyl-β-cyclodextrin; sulfobutylether-β-cyclodextrin